Interface reaction between an electroless Ni–Co–P metallization and Sn–3.5Ag lead-free solder with improved joint reliability - Yang, Ying (2014)
To address the reliability challenges brought by the accelerated reaction with the implementation of lead-free solders, an electrolessly plated Ni-Co-P alloy (3~4 wt.% P and 9~12 wt.% Co) was developed as the solder metallization in this study. Three compounds layers, (Ni,Co)3Sn4, (Ni,Co)3P and (Ni,Co)12P5 are formed at the reaction interface. Nano-sized voids are visible in the (Ni,Co)3P layer under TEM, but no large voids are found under SEM. This is an indication of effective diffusion barrier performance by the Ni-Co-P metallization than the binary Ni-P metallization. The influence of interfacial reaction on the solder joint reliability was reported through the evaluation of the tensile strength of micro solder joints. Upon aging at 180 C for 600 h, the tensile strength of Ni-Co-P/Sn-3.5Ag solder joint remains high, and the failure is caused by the bulk solder necking and collapse. As a comparison, the tensile strength of Ni-P/Sn-3.5Ag solder joint drops significantly after aging for 400 h at 180 C, and the fracture mode has shifted from ductile failure in the bulk solder to the brittle failure at the solder joint interface. The Ni-Co-P metallization, having a much slower consumption rate and improved resistance to joint strength degradation during long-term aging treatment, is a potential candidate for future microelectronic solder metallization materials.